NGO Strategies to Intervening in Agricultural Value Chains for Development of Small Producers with the Private Sector: Examination of Oxfam Ethiopia’s Approach - Eworo, lucy (2009)
There is a growing recognition of the potential value of integrating small producers into the agricultural value chains of private companies. However there are also challenges that affect such integration strategies. Thus an analytical framework was developed combining the strategic approaches used by NGOs’ to examine the intervention activities of Oxfam Ethiopia to agricultural value chain development with the private sector. The results showed that negative factors in the business environment play a major role to hindering the intervention activities of the NGO. This then leads to the assumption that total funding or subsidizing the activities will encourage the involvement of the private companies, however this limits the pace and scale of resource commitment. Having also identified alternative solutions that could avoid such issues, it was concluded that NGOs’ need to embrace new ways of facilitating the creation of more innovative and sustainable supporting mechanisms. That would not only encourage the involvement of the private companies but also empower the small producers. This paper seeks to provide a better understanding of the approaches to agricultural value chain development and also serves as a basis for further research in the field.